The History of Natural Sciences as a component of the hidden curriculum - S. Yu. Kryzhanovskaya; Ya. V. Bulgakova; A. I. Filipchenko (Высшее образование в России)
The history of the development of natural sciences is integrated into the educational process of the relevant disciplines and can influence the formation of a student’s personality. The content and interpretation of the historical component are not regulated, they are included in the “hidden curriculum”. The purpose of the work is to analyze the functions of history in the teaching of natural sciences as a component of the hidden curriculum according to literature data and to assess the degree of their implementation in the opinion of participants in the pedagogical process. Results. At the first, we highlighted the functions that history performs within the framework of natural sciences based on the literature data. Then during empirical stage in 2022 we conducted the anonymous online survey of tutors and students of 2-3 courses of Russian medical universities (N=325). The analysis of the obtained data showed that, according to the survey participants, firstly, the history of the studied science is a necessary part of the educational process. Secondly, the use of historical facts during lectures and classes performs more cognitive (including the development of critical thinking) than educational functions (including the formation of socio-cultural identity and citizenship), which can be associated with varying degrees of their implicitness. The results of the survey of students from different regions turned out to be similar. Most of the respondents supported the unification of the historical component of the natural science discipline for all medical universities in Russia. In a practical sense, the results of this study can be used in the training and advanced training of university teaching staff in order to focus on the hidden components of the educational process and actualize various contexts of the history of natural sciences, as well as be taken into account in the development of educational literature and work programs. The externalization of the hidden curriculum will allow to integrate it into a unified educational policy.